Using real world evidence to generate cost-effectiveness analysis of fibrinolytic therapy in patients with ST-segment elevation myocardial infarction in Thailand - Krittimeth Trerayapiwat; Peerawat Jinatongthai; Prin Vathesatogkit; Piyamitr Sritara; Ninutcha Paengsai; Piyameth Dilokthornsakul; Surakit Nathisuwan; Lan My Le; Nathorn Chaiyakunapruk (Elsevier, 2022)
Summary: Background: Due to limited access to primary percutaneous coronary intervention for the management of ST-segment elevation myocardial infarction (STEMI) in low-to-middle-income countries (LMICs), fibrinolysis serves as a vital alternative reperfusion therapy. Among fibrinolytic agents, the cost-effectiveness of tenecteplase (TNK) in LMICs as compared to streptokinase (SK) for STEMI management remains unknown. Methods: Cost-effectiveness was analyzed using a hybrid model consisting of short-term analysis (30-days decision tree model) and long-term analysis (Markov model). Both health care provider and societal perspectives over a lifetime horizon with 3% discount rate were considered. Input parameters were obtained from Thailand's national health database, a network meta-analysis and literature review. Outcome measure was an incremental cost-effectiveness ratio (ICER) determined by an incremental cost per quality-adjusted life years (QALY) gain. An ICER of less than $5,590 per QALY gain is considered cost-effective. Series of sensitivity analyses were also performed. Findings: From the societal perspective, TNK increases cost by $827 and increases QALY by 0·173. Thus, the ICER is $4,777 per QALY gained. Similarly, the ICER from health care provider perspective is $4,664 per QALY gained. In the probabilistic sensitivity analysis, using 5,590 USD per QALY as threshold, the probability of TNK being cost-effective was 83% from both perspectives. The most influential parameters were risk ratio of death for treatment with TNK compared to SK and drug cost of TNK. Interpretation: In a resource-limited country like Thailand, tenecteplase is a cost-effective fibrinolytic drug for treatment of STEMI compared to streptokinase. Funding: None.